Corporate Governance Mechanism and Corporate Social Responsibility on Firm Value - Jacobus Widiatmoko (Relevance: Journal of Management and Business, 2020)
This study aims to empirically examine the effect of corporate governance and corporate social responsibility on corporate value using agency perspectives and stakeholder theory. Corporate governance is measured using an independent commissioner, a board of directors, and an audit committee. The research data were obtained from manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The test results using multiple linear regression indicate that corporate governance as measured by the board of directors and audit committee has a positive effect on company value. Meanwhile, the existence of independent commissioners in the sample companies did not have an impact on increasing the value of the company. The same result also occurs for CSR variables, which have not been proven to affect the firm's value. The results of the sensitivity analysis show that the research model is robust, both by measuring PBV or Tobin's Q for the dependent variable. Keywords: independent commissioner, board of directors, audit committe, corporate social responsibility, firm value